Marsupialization: A conservative approach for treating dentigerous cyst in children in the mixed dentition (Case Report). (Journal of Hama University, 2021)
Dentigerous cysts are the most common developmental odontogenic cysts of the jaw and are usually encountered in the practice of pediatric dentistry. The treatment modalities range from marsupialization to enucleation of the lesion and are based on the involvement of the lesion with the adjacent structures. However, loss of a permanent tooth in the management of a dentigerous cyst can be devastating to a child marsupialization is the prefer modality for treatment . This case describes the technique of marsupialization in which we extracted the deciduous first and second molars and created a window through the extracted socket to decompress the lesion. After 6 months the first and second premolars erupt in the oral cavity and bone healed completely on panoramic radiograph